THE HALF-BLOOD HERO IN Y. B. MANGUNWIJAYA’S IKAN- IKAN HIU, IDO, HOMA AND JAMES CAMERON’S AVATAR - Nikodemus Yudho Sulistyo (STBA Pontianak, 2017)
Heroism is a noble deed full of courage and bravery to protect the weak and the oppressed. The heroes have been known throughout the centuries, through the history records, artworks and literary works. Heroes have been de- scribed as having perfect physical appearance and strength. However, there are also depictions that a hero has a dilemma when he has the half-blood descendant of both the people he fights for and the enemy he fights to. In this research, the writer analyzes the half-blood hero in Y. B. Mangunwijaya’s novel, Ikan- IkanHiu, Ido, Homa and compares it to James Cameron’s movie, Avatar. The writer uses Structuralism and Semiotics approaches to find the heroic symbols and signs, compare them and find the particular structure. The result can be found that the half-blood heroes both in the novel and movie have the prominent physical appearance of superiority and strength compared to others. They also deal with the dilemma in status and position in the society as the half-blood or mixed-blood heroes, and they hold the heroic principles such as bravery and the ideal of protecting the weak and fight for the oppressed.